Theoretical investigations of experimentally-observed Open-Circuit Voltage-Decay (OCVD) curves - Gopal R.; Dwivedi R.; Srivastava S.K. (My University, 2025)
The study of the open-circuit voltage-decay (OCVD) curve has significant importance for determining the minority carrier lifetime in the quasineutral base of a semiconductor diode. Different models, proposed earlier, have provided a basis for explaining the experimental results. However, the observed peculiar nature of the curves cannot be fully explained in terms of phenomena associated with base and depletion regions. In the present work, a theoretical analysis has been carried out to investigate the possible mechanisms responsible for the observed peculiarities in the OCVD curves, by including the transition carrier capacitance of the depletion region. This capacitance has been used in addition to the well-known and widely discussed effects, such as the space-charge capacitance due to ionized impurities, recombination current, and base region effects. The inclusion of the transition carrier capacitance has been done for the first time. © 1983.